Pengaruh Capital Intensity Leverage Dan Profitabilitas Terhadap Tax Agresivitas Dengan Kinerja Pasar Sebagai Variabel Moderating - Desi Natalya (Universitas 17 Agustus 1945 Jakarta, 2018)
This study is a study of the effect of Capital Intensity, Leverage, and Profitability on Tax Aggressiveness with Market Performance as a moderating variable. This research was conducted on Manufacturing companies in the industrial goods consumption sector in 2010-2016 with the selection of samples using purposive sampling method and producing 20 companies to be studied. Capital Intensity, Leverage and Profitability are measured by percentage of ownership, effective tax rate is proxied by ETR, Market Performance is proxied by Tobins'Q. The results of this study are that Capital Intensity has a significant effect on Tax Aggressiveness, Leverage has a significant effect on Tax Aggressiveness, Profitability has no significant effect on Tax Aggressiveness, moderation Market performance is not able to strengthen the influence of Capital Intensity on Tax Aggressiveness, moderation Market performance is not able to strengthen the influence of leverage on tax aggressiveness and moderation Market performance is able to strengthen the influence of profitability on tax aggressiveness.Keywords: Capital Intensity, Leverage, Profitability, Tax Aggressiveness, Market PerformancePengaruh Capital Intensity Leverage Dan Profitabilitas Terhadap Tax Agresivitas Dengan Kinerja Pasar Sebagai Variabel Moderating